Emotional intelligence on burnout : the mediating role of work – life balance - Hilya Ghevira; Okki Trinanda (Universitas Negeri Padang, 2022)
The purpose of this study was to analyze the effect of emotional intelligence on burnout in the area of ​​PT Pegadian (Persero) Padang through work-life balance as a mediator. The population of this study were 43 people,, with all employees in ​​PT Pegadaian (Persero) Area Padang. The sample size for this study was determined using a total sampling appropriate to a population of 43 people. The analytical method used in this research is using SEM analysis with SmartPLS-3. The results of this study indicate that there are: Emotional intelligence has a negative significant effect on burnout. Emotional intelligence has a positive significant effect on work-life balance. Work-life balance has a negative significant effect on burnout. Emotional intelligence has a significant effect on burnout through a balance between work and life as a mediator.